LIMBAH PASAR SEBAGAI SUBSTITUSI DEDAK DALAM RANSUM ITIK HIBRIDA FASE GROWER - Erna Yuniati; Anifiatiningrum; Ardina Tanjungsari; Nur Solikin; Charisa Fitri Ramadhan; Melati Ariana (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2026)
Feed costs are a major factor affecting the efficiency of duck farming. Market waste in the form of vegetable and fruit scraps has the potential as an alternative feed ingredient because it has a nutrient content that can be utilized by livestock and can reduce environmental pollution. The study aims to determine the effect of market waste with bran substitution on the performance of hybrid ducks in the grower phase. The study used 36 3-weekold hybrid ducks raised for 4 weeks with a Completely Randomized Design (CRD), with 4 treatments and 3 replications. The treatments consisted of Kontrol/P0 (100% bran), P1 (90% bran + 10% market waste), P2 (80% bran + 20% market waste), and P3 (70% bran + 30% market waste). The research indicators were ration consumption, livestock weight gain, and ration conversion. The results showed that market waste as a bran substitute affected ration consumption, but did not affect body weight gain and ration conversion. Market waste can be used as much as 30% without reducing the performance of hybrid ducks in the grower phase. Keywords: hybrid ducks, market waste, bran substitution, performance, feed rations